Risk of Narrow Upper Airway in Class II Children with Large Horizontal Maxillary Overjet Assessed By Acoustic Reflection: a Case-Control Study - Camilla Hansen; Merete Bakke; Liselotte Sonnesen (Stilus Optimus, 2024)
Objectives: The aim of this case-control study was to examine upper airway by acoustic reflection in class II children with large horizontal maxillary overjet compared to children with neutral occlusion. Material and Methods: The study group included children of 9 to 14 years with class II and large horizontal maxillary overjet (≥ 6 mm) with indication for growth adaptive treatment of the mandible compared to children with neutral occlusion (controls). Acoustic pharyngometry and rhinometry were performed in natural head position. Differences between groups were tested by chi-square test, general linear model (adjusted for age, gender and body mass index [BMI]), and Mann-Whitney test. Results: The study and control group consisted of 37 (male 19, female 18) and 32 (male 16, female 16) participants, respectively. No significant differences in age, gender, and BMI were found between the groups. For the acoustic rhinometry measurements significantly increased resistance (P = 0.04), reduced volume (P = 0.03) and distance to minimal cross-section area (MCA) (P = 0.035) were found in the study group, but only for the right nostril. However, significantly reduced MCA for both nostrils was found in the study group compared to controls (P = 0.025 to 0.04). No significant differences in acoustic pharyngometry measurements were found. Conclusions: Nasal airway dimensions were significantly reduced and nasal resistance was significantly increased in the study group compared to controls. Thus, class II and large overjet with indication for growth adaptive treatment may be a risk factor for sleep-disordered breathing in children. The results may prove valuable in non-invasive risk assessment of narrow upper airway in children with class II and large overjet.